Liquid regulation: the (men's) business of women's water music?. Issue 2 (June 2022) - Forsyth, Miranda; Dick, Thomas
Abstract: Complexity and uncertainty often animate the desire for regulatory approaches seeking to fix, limit and constrain. But what if, instead of doubling down on 'solid' regulation, we also make room for 'liquid' regulatory approaches? We interrogate this question through deep empirical analysis of the developing regulatory framework around a form of Melanesian cultural property known as water music. We argue that, although both solid and liquid regulatory forms exist in all normative orders, we have recently seen an increasing emphasis on solid forms of regulation (legislation, registers, etc.) with respect to cultural property. As an effort to consider alternative approaches, we identify a range of liquid regulatory strategies drawing from our case-study. We show how attention to temporality, relationality and situatedness can impact upon the degree of liquidity of individual regulatory approaches, and how they can cumulatively impact the solidity or liquidity of the overall regulatory system. Finally, we identify the different ways in which gendered power and forms of accountability emerge in contexts of solid or liquid regulatory strategies.